The Management of Physical Evidence and Chain of Custody (CoC) in Digital Forensic Laboratory Storage - Tino Feri Efendi (International Journal of Seocology, 2019)
Computer crime has 2 types of evidence, namely: physical evidence and digital evidence. Storage on physical evidence requires a special space that can hold physical evidence. However, a system that can store and manage physical evidence is needed.The current problem is the absence of a concept of storing physical evidence and its documentation (Chain of Custody). Management of Physical Evidence is proposed as a solution to solve the problem. This concept is in the form of a Physical Evidence Management System and Chain of Custody by taking the analogy of a Data Inventory. Problems with Physical Evidence Management require a Management System for Physical Evidence that is suitable for use in the UII Digital Forensics Laboratory. This research has successfully implemented the concept of Data Inventory. It is expected that with the concept of Physical Evidence Management the control of physical evidence and all activities related to it can be maintained and documented properly.